'Cruise-and-Collect' algorithm for an ARM-based autonomous robot - Zarina, Mohd. Noh; Sani Irwan, Md. Salim; Norhidayah, Mohamad Yatim; Nur Alisa, Ali; Muzalifah, Mohd. Said (2012)
The 'cruise-and-collect' algorithm proposes in this research is intended to be applied for autonomous robot system. The robot is designed to be used in a sport such as table-tennis, to help the players collect the off-side ball during a game. The controller for the robot system will utilize ARM-based microcontroller chip from Atmel, AT91SAM7S128, as it is the classic ARM7TDMI processor that had marked a great success of ARM processor market. The algorithm is developed via Flowcode software which exploits flowchart as its design entry. The E-block board that has an integrated microcontroller chip is used for the purpose of its hardware prototype and software testing. It is hoped that the development and design process exposed in this research will be benefitted for researchers who are interested in the area of prototype development and robot design, especially via the ARM7TDMI processor platform.